Revolutionary Movements in different part of Iran 1918-24 - Khandagh, Najleh (Advances in Social Sciences Research Journal, 2015)
The revolutionary movements formed – in Gilan , Azerbaijan , Khurasan and Khuzestan – primarily to fight foreign intervention in Iran and for an end to Iranian tyrannical rule which oppressed its people . These aim banded people together and thus furthered the development of the revolutionary movements in different part of Iran between 1918 -24. . All revolutionary movement were ultimately defeated in turn by internal reactionary forces and their Western backers , and its own tactical errors. It is appropriate to divide the reaction against the revolutionary movements into two parts , internal and external . These correspond to pressure which came from within Iran , primarily from the central government , and to international coverage of the movements , both from the West and from the Soviet Union . At points , the two aspects into one and we will indicate as much . The central governments played a major role in the reaction against the revolutionary movements on two fronts , as it were . The immediate policy adopted by the central governments towards the revolutionary movements was suppression leading to its elimination . The campaign had been initiated by action against progressive and radicals movements throughout Iran . During the crisis , the soviet Union professed to regard the revolutionary movements in Iran as a democratic movements struggling against the reactionary approach of the central government , and treated it as legitimate indigenous demand for local rights